Semiotics and Hermeneutics of the Everyday. - Paschalidis, Gregory (Cambridge Scholars Publishing, 2015)
The linchpin of the momentous paradigm shift that produced the new hermeneutics of everyday life was a focus on people as active agents in various cultural contexts, uses and practices, the merging of the conventional distinctions between the private and the public, the local and the global, the material and the symbolic, and the bridging of the agency/structure divide marking grand historical and cultural narratives. In their place, a wealth of new kinds of narratives were produced out what ...